Changing the Face of Health Education via Health Interventions: Social Ecological Perspectives on New Media Technologies and Elementary Nutrition Education. Issue 13 (10th November 2019) - Bissell, Kimberly; Baker, Kim; Pember, Sarah E.; Zhang, Xueying; Yang, Yiyi
ABSTRACT: The relationship between media use, family dynamics, and school environments on a child's likelihood to be overweight or obese is an area of research with limited empirical evidence; however, reports have indicated that children are increasingly developing more negative habits related to their health. The purpose of the present study was to employ a social ecological perspective in determining the effectiveness of a longitudinal health literacy/health intervention program on children's nutritional knowledge, attitudes toward healthy eating and exercise, food preferences, and eating behavior. Using a sample of elementary school children initially in Grades 2 and 3 and then in Grades 3 and 4, a field experiment was conducted using a new media technology to record their food intake at home and at school. Results from the study suggest that the health literacy program was successful with positive increases observed for cognition, attitudes, and behavior. From a perspective of social ecological model, the findings suggest that children's eating behaviors need to be considered at the intersection of children's health literacy/attitudes, community efforts, and media/screen time use.